Training in ethical judgment with a modified Potter Box. (January 2014) - Watley, Loy D.
<x xml:space="preserve">Abstract</x> After a brief review of the ethical judgment research, the Potter Box, a four‐step ethical judgment tool used primarily in media ethics, is introduced. The paper proposes that the Potter Box's usefulness for evaluating ethical dilemmas could be improved by re‐sequencing the steps, by incorporating philosophical intuitionism as a mechanism for structuring its inherent pluralism and by adding a post‐decision, pre‐action reflective step. The resulting modified Potter Box has five steps – analyze the situation, identify stakeholders, specify duties, weigh obligations and check for universalizability – and should provide a useful structure for analyzing difficult ethical dilemmas and for creating transparency in the judgment process that accommodates improved discussion.